2009
DOI: 10.1111/j.1365-2605.2008.00926.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between varicoceles and obesity in a young adult population

Abstract: To determine whether a relationship between obesity and varicocele occurrence exists, the prevalence and severity of varicoceles related to obesity were investigated in a general population of young males. A total of 1050 young males attending the Navy Recruit Training Center were evaluated from their physical screening examinations. All subjects underwent history taking and physical examinations to evaluate for the presence and severity of varicocele. The anthropometric indexes including body mass index (BMI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 25 publications
4
50
0
1
Order By: Relevance
“…Three of them reported that there were no statistically significant differences between the two groups with respect to height, whereas six indicated that the patients with varicocoele were significantly taller than controls, which is similar to our study. The latter result has led to speculation that greater overall height was associated with an increased hydrostatic pressure in the spermatic vein, predominantly on the left side, which may in turn overwhelm the valve mechanisms in the veins, resulting in the development of varicocoele (Tsao et al, 2009). The findings of our study support the concept of a statistically positive relationship between varicocoele and height.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Three of them reported that there were no statistically significant differences between the two groups with respect to height, whereas six indicated that the patients with varicocoele were significantly taller than controls, which is similar to our study. The latter result has led to speculation that greater overall height was associated with an increased hydrostatic pressure in the spermatic vein, predominantly on the left side, which may in turn overwhelm the valve mechanisms in the veins, resulting in the development of varicocoele (Tsao et al, 2009). The findings of our study support the concept of a statistically positive relationship between varicocoele and height.…”
Section: Discussionsupporting
confidence: 80%
“…In 12 studies: first, no significant differences in BMI were detected (Delaney et al, 2004;Kilic et al, 2007), secondly, patients with varicocoele had a distinctly lower BMI (May et al, 2006;Baek et al, 2011), and thirdly, the number of the varicocoele patients decreased as the BMI increased, as found by others (Handel et al, 2006;Nielsen et al, 2006;Prabakaran et al, 2006;Kumanov et al, 2008;Tsao et al, 2009;Al-Ali et al, 2010;Chen & Huang, 2010;Hassanzadeh et al, 2011;Soylemez et al, 2012) and us. It is clear that obesity may lead to decreased detection of varicocoele, even in our study, because of difficulty in palpation on physical examination.…”
Section: Discussionsupporting
confidence: 55%
“…Celiktas M, and associates have shown a decreases in varicocele incidence in obese men due to the increased retroperitoneal fat thickness and the adipose tissue deposition within the inguinal cord structures and scrotal content [17]. The present data support the explanation that obesity may result in a decreased nutcracker effect, which accounts for prevention of the renal vein compression by the adipose tissue [18]. Albert O, and associates in 2013, has published an interesting article to point up [19].…”
Section: Commentarysupporting
confidence: 76%
“…Several molecules, such as insulin, oestrogens, leptin, tumour necrosis factor a (TNFa) or other adipokines, mainly related to increased adiposity, have been hypothesized to induce MetS-related hypogonadism, acting both at a central or at a peripheral level (see for review Corona et al, 2011b). In contrast with the positive association between hypogonadism and MetS, varicocoele was less often found in subjects fulfilling MetS criteria, thus confirming the view that obesity is a protective factor against varicocoele (Handel et al, 2006;Nielsen et al, 2006;Tsao et al, 2009).…”
Section: Discussionmentioning
confidence: 54%